Exceptional flooding tolerance in the totipotent recalcitrant seeds of Eugenia stipitata. Issue 2 (9th May 2017) - Calvi, Geângelo P.; Anjos, Antônio M. G.; Kranner, Ilse; Pritchard, Hugh W.; Ferraz, Isolde D. K.
Abstract: Eugenia stipitata occurs along rivers in Western Amazonia and produces berry-type fruits with economic potential. Its large recalcitrant (i.e. desiccation-intolerant) seeds have been proposed as a model to study seed stress response, as no apparent differentiation between the embryonic axis and the fused cotyledons are visible. Here, the longevity of submerged seeds was analysed with a view to understanding adaptive mechanisms to seasonal flooding. Submerged seeds began germinating after 2 months. After 1 year, 87 and 96% total germination was reached when seeds were submerged under a water column of 6 cm (where seedlings could emerge from under the water) and 26 cm (where seedlings could not reach the water surface), respectively. Seedling morphology was altered underwater, with short internodes and rudimentary leaf blades, and when submersion was terminated, seedlings transplanted to nursery conditions recovered a normal phenotype. Furthermore, when seedlings were detached from the seeds, the 'resown' seeds produced a second, normal seedling within 9 months. Concentrations of the antioxidant glutathione, which was measured as a stress marker, increased with submersion time in water. Seeds that had developed roots and shoots underwater had higher concentrations of glutathione disulphide than non-germinated seeds, suggesting that the flooding stress was more intense for seedlings than seeds, although more oxidizing cellular redox environments are also consistent with the conditions required for differentiation. Submergence underwater is recommended for storage of the recalcitrant seeds of E. stipitata for up to 1 year.